Peningkatan Prestasi Belajar PAI Melalui Pembelajaran Mastery Learning Dengan Metode Drill - Nafsiah Nafsiah (GHIROH, 2022)
This classroom action research focuses on improving student achievement in Islamic Religious Education learning which aims to determine whether the application of the Mastery Learning learning model with the Drill method (Exercise) can improve student achievement for Islamic Religious Education subjects in grade II SD. To answer this question, a classroom action research was conducted with a descriptive qualitative data analysis method. The results of the data analysis showed that students experienced an increase in their learning achievement after applying Mastery Learning with the Drill method. This happens because during the learning process students become more active, enthusiastic and can understand the material being taught as a whole so that student learning achievement increases. This research has been able to prove the main effect of the Mastery Learning learning model in improving learning achievement, it is certain that in this study there are still things that have not been perfectly done, therefore it becomes a suggestion for other researchers who are interested in researching the same topic for future research. will come.